Application of the Cambodian Constitution - Vandanet Hing (Journal of Southeast Asian Human Rights, 2019)
Studies conducted on the constitutional law-making process have shown that public participation is a key element of the relationship between the government and its citizens, and legitimizes the whole process. The present paper discusses the relationship between the people and the government on the basis of the Cambodian Constitution, both de jure andde facto. As assessments, it takes the 1993 constitutional making process and the public’s participation thereto. This paper aspires to answer the following questions: firstly, how does the constitutional law-making process impact the exercise of constitutional rights in Cambodia, and, secondly, to what extent does public participation play a role in public affairs, especially insofar as the constitution and law making processes are concerned. It further suggests that the concept of meaningful public consultation on constitution and law making should be incorporated in the Cambodian Constitution.